Newly recorded plant-aphid associations: Implications for PLRV and PVY control in potato crops - Machado Assefh, Cristina R. (2023)
The most important viral diseases in potato crops are PVY and PLRV, and they are efficiently transmitted by numerous aphids being Myzus persicae and Macrosiphum euphorbiae, the most important. These vector aphids are highly polyphagous and are widely distributed; and since PVY and PLRV have a broad host range there can be a wide diversity of plants hosting vector aphids, and/or being reservoirs of the viruses, in the community of plants associated with potato crops. Here, we searched for plants growing in the areas adjacent to potato crops in Salta, Argentina, to find plants that represent a risk for potato crops for being hosts of aphid vectors and/or reservoirs of PLRV and PVY. We found 34 plant species belonging to 16 families hosting aphids, from these 11 plant species were reported as hosts for PVY and/or PLRV. Also, we found 27 aphid species and 18 of them have been reported as vectors for PLRV and/or PVY. Three aphid species were found on most plants; M. persicae, M. euphorbiae and Aphis gossypii. Altogether, we found 95 plant-aphid associations in potato fields, of which 16 are newly recorded plant-aphid associations. These new associations likely arose from the great diversity of plants hosting a great diversity of aphids reported as vectors of PLRV and PVY, in a changing and dynamic agricultural ecosystem. The results that we present have implications for PLRV and PVY control in potato and other related crops.